Loneliness, Implicit-Self and Digital Literacy - Ko, Dong Woo; Lee, Ji-yeon; Kim, Hyesuk (Frontiers in Psychology, 2022)
Digital literacy is becoming more important because of the skillset of functioning in online is becoming a necessary skill set in daily life. The purpose of this study was to examine the association between loneliness and digital literacy and the mediation effect of motivation in that association. Also, this study examined the moderating effect of mindset in the meditation effect of motivation in the association between loneliness and digital literacy. 287 respondents were recruited from online survey in U.S. To investigate the direct effect of loneliness on digital literacy, the mediating effect of motivation, and the moderating of mindset on the mediating effect, this research employed a mediated moderation model. The findings of this research suggest that prevention-focused motivation mediated the effect of loneliness on digital literacy and the effect was moderated by a fixed mindset (as opposed to a growth mindset). The result of the study contributes to the literature by examining how loneliness could impede acquiring digital literacy through prevention-focused motivation and fixed mindset.